Nghiên cứu tổng hợp các hybrid mới của artemisinin với zidovudin (AZT) - Bình, Lê Huy; Tiến, Vũ Đình; Tiến, Hoàng Xuân; Vũ, Trần Khắc (Vietnam Journal of Chemistry, 2016)
The synthesis of new hybrids of artemisinin with zidovudin (AZT) was described via six-step procedure. Firstly, the reaction of dihydroartemisinin (2) with NaN3 in the presence of (CH3)3SiCl and a catalytic amount of KI in CH2Cl2 at ice water temperature gave 10β-azidoartemisinin (4). This compound was then hydrolysed by Ph3P in THF/H2O at 65 oC for 6 h to furnish 10β-azidoartemisinin (5). Next, the reaction of 5 with anhydride dicacboxylics (anhydride glutaric, 3,3-dimethyl anhydride glutaric) in the presence of DMAP gave new intermediates 7a,b. Compound 6 was obtained by the reaction of 5 with suberic acid monomethyl ester in CH2Cl2 in the presence of EDC and DMAP at ambient temperature, followed by the hydrolysis in CH2Cl2/EtOH = 9:1 using NaOH 0.2 N. Finally, the reaction of 6 and 7a,b with AZT in CH2Cl2 using EDC and DMAP as a catalytic system afforded novel hybrids 8a-c in moderate yields. The structures of synthesized compounds were confirmed based on spectroscopic methods: IR, NMR and HRMS. Keywords. Artemisinin, dihydroartemisinin, artemether, arteether, sodium azide, hybrid.